The Power of Domestic Violence and Abuse Counter Narratives: Telling Stories in Parliamentary Debates - Shaw, Rebecca (Narrative Works)

(untitled) (Centre for Digital Scholarship, University of New Brunswick, 2024)
This paper sets out to interrogate the use of master and counter narratives in UK Parliamentary Select Committee debates surrounding the passage of the Domestic Abuse Bill (now Domestic Abuse Act 2021) in Parliament. These debates are a site that allow for the telling of counter narratives in order to challenge the narrative of the normative socio-legal position regarding domestic violence and abuse (DVA). With its roots in the patriarchy and stereotypical gender roles that foster violence and abuse, the issue with such a narrative is that it fails to recognise the complex, nuanced nature of domestic violence and abuse. As a result, it maintains the status quo and is disconnected from the realities of DVA. The work of this paper, then, is to consider the dialogue between the masterplot of DVA, the Domestic Abuse Bill, and the attempts of counter narratives to act as discursive resistance. It will consider what is the true power of these anti-hegemonic stories in exposing the problems with the master-narrative. Counter narratives submitted by organisations, activists, academics and survivors of DVA during the Committee Stage of the debates were not uniform, monolithic or pure, and were often plagued with inconsistencies and contradictions with one another. Characterised as the same but different, these counter narratives did not act in strict opposition to the hegemonic master narrative. As a result, this paper will draw on a case study which examines three different reports submitted during the Committee Stage of the Debates to consider the following questions: in what way can counter narratives act as discursive resistance in law reform efforts and why are some more successful than others in dismantling the master narrative through the mechanism of the law? Overall, the argument put forward is that it is the counter narratives with a greater illocutionary force and greater narratological power which can be a successful tool in law reform and effect a shift in the master narrative of domestic violence and abuse.